2013
DOI: 10.1002/app.40030
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical, dielectric, and electromechanical properties of silicone dielectric elastomer actuators

Abstract: Silicone elastomer actuators were investigated to develop a simple and industrially scalable product with improved mechanical properties, such as a low modulus, high tearing strength, and good resilience, and enhanced electromechanical actuation properties. Silicone elastomers were fabricated via a hydrosilylation addition reaction with a vinyl-end-functionalized poly(dimethyl siloxane) (V), a multivinyl-functionalized silicone resin, and a crosslinker in the presence of a platinum catalyst. For the larger ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…4 times lower than PTMDMT1 (0.658% at 50 V pp μm −1 ), probably due to the lower dielectric constant obtained without a controlled morphology. 17 In this regard, the concept of methacrylatebased triblock-random copolymers can be a promising platform to solve the recent issues raised in electroactive elastomers.…”
Section: Synthesis Of Triblock-random and Triblock Copolymersmentioning
confidence: 99%
“…4 times lower than PTMDMT1 (0.658% at 50 V pp μm −1 ), probably due to the lower dielectric constant obtained without a controlled morphology. 17 In this regard, the concept of methacrylatebased triblock-random copolymers can be a promising platform to solve the recent issues raised in electroactive elastomers.…”
Section: Synthesis Of Triblock-random and Triblock Copolymersmentioning
confidence: 99%
“…Dielectric electro active polymer (DEAP) is able to respond sensitively to environmental humidity, temperature, pH value, light conditions, or changes in external environment such as magnetic field, electric field, microwave and ultrasonic radiation 1–3 . Because the DEAP is capable of simplifying the mechanical structure and improving the energy conversion rate, it is widely used in many scientific fields of bionic engineering, Micro‐Electro‐Mechanical System (MEMS), flexible robots, wearable sensors, electric control valves and biological medicine etc 4–7 .…”
Section: Introductionmentioning
confidence: 99%
“…In view of this, international researchers have designed a series of electronic or ion gel actuators, inspired by the composition of human muscle and its actuated principle. [9][10][11] Tang, Wang and Yang et al [12][13][14] have prepared a Poly(Vinylidene Fluoride) (PVDF)/Poly(Ethylene Glycol) Diacrylate (PEGDA)/Polymethyl Methacrylate (PMMA) gel actuator compounded with graphene, whose the highest ionic conductivity is about 4.63 Â 10 À3~1 0 À6 S/cm and the electrochemical window is 4.5 V. Sheela et al 15 has adopted a solution casting technology to successfully fabricate the polyvinyl alcohol/Sodium Alginate (SA) blends doped with different concentrations of NaClO 4 , which shows that with its doping content increasing, the dielectric constant declines as well as the dielectric loss and alternating current conductivity rise. Kim and Wang et al 16,17 have reported a kind of SA-polydiallyldimethylammonium chloride hydrogel that is able to produce large deflection in 0.6 wt% HCl solution and is positively correlated with the applied voltage.…”
Section: Introductionmentioning
confidence: 99%